2010
DOI: 10.1590/s0102-695x2010000300015
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of two species of the genus Alchornea measured by Salmonella microsome assay and micronucleus test

Abstract: Some species of the plant genus Alchornea (family Euphorbiaceae) are widely used in popular medicine, mainly in South America and in Africa. Several kinds of biological activity have been seen in the species: antioxidant, antifungal, anti-inflammatory, antibacterial, cytotoxic against tumor cell lines and inhibitory to the replication of HIV-1 and HIV-2. In Brazil, the species Alchornea castaneaefolia Willd. A. Juss. and Alchornea glandulosa Poepp. & Endl. are used by the local population to treat rheumatism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Other studies have demonstrated that natural products can represent serious risks to the DNA integrity of different organisms. 31,32 The methodology employed herein affirms that the extract of P. torta is mutagenic in vivo and in vitro in the absence of metabolic activation. The in vivo test would reflect the metabolism of the active constituents and the metabolization is more complex.…”
Section: Mutagenicity Assayssupporting
confidence: 56%
“…Other studies have demonstrated that natural products can represent serious risks to the DNA integrity of different organisms. 31,32 The methodology employed herein affirms that the extract of P. torta is mutagenic in vivo and in vitro in the absence of metabolic activation. The in vivo test would reflect the metabolism of the active constituents and the metabolization is more complex.…”
Section: Mutagenicity Assayssupporting
confidence: 56%
“…The mutagenic index (MI) was also calculated for each dose, as the average number of revertants per plate divided by average number of revertants per plate of the negative (solvent) control. A sample was considered positive when MI≥2 for at least one of the tested doses and if the response was dose dependent (Varella et al, 2004;Santos et al, 2010).…”
Section: Ames Mutagenicity Assaymentioning
confidence: 99%
“…Several plants have been used as folk medicine for the treatment of several diseases (Melo-Reis et al, 2011), some of which, such as Solanum validinervium (Suarez et al, 2006), Morinda citrifolia (Brito et al, 2009) and Annona squamosa (Nandhakumar & Indumathi, 2012), showed highly interesting characteristics, while others, such as Bauhinia monandra (Macêdo et al, 2008), Alchornea grandulosa, A. castaneaefolia (Santos et al, 2010) and Cochlospermum regium (Castro et al, 2004;Andrade et al, 2008), proved to be genotoxic.…”
Section: Introductionmentioning
confidence: 99%